A review of Deep Learning Privacy, Security and Defenses - Dawood, Afrah Salman; Hadi, Noor Kadhim (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Deep learning (DL) can be considered as a powerful tool in different fields and for different applications but its importance raised the concern about privacy, security, and defense issues. This research presents an important overview about different aspects and state-of-the-art techniques in DL privacy, security, and defense. Wide range of topics was covered including private data frameworks, different types of threats and attacks, and the most important defense techniques. We have also discussed the challenges and limitations of each approach besides to possible future research directions. This survey can be considered as a comprehensive guide for other researchers and policymakers who are interested in understanding these important topics associated with DL.